2015
DOI: 10.1021/acs.energyfuels.5b00172
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted–Lewis Acidic Ionic Liquids and Application in Oxidative Desulfurization of Diesel Fuel

Abstract: Study on alternative methods to hydrodesulfurization is always an interesting area, because of the ineffectiveness for hydrodesulfurization to remove some cyclic sulfur compounds (S-compounds) and the high cost from harsh operation conditions and expensive catalyst, among which oxidative desulfurization (ODS) using ionic liquids (ILs) as solvent is intensively studied recently. Here, we synthesize a series of Brønsted–Lewis acidic ILs of N-methylpyrrolidonium zinc chloride ([Hnmp]­Cl x /(ZnCl2) y , x:y from 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…In addition, higher temperature may decrease the viscosity of ILs, enhance effective mixing and inter-phase mass transfer, and H 2 O 2 may be used effectively after decomposition. [50][51][52] On the other hand, too high temperatures are not good choice and might lead to auxiliary risk of explosion in the process, although high temperature enhances H 2 O 2 decomposition. Therefore, reaction at higher temperature should be carefully avoided.…”
Section: Ods Using Ilsmentioning
confidence: 99%
“…In addition, higher temperature may decrease the viscosity of ILs, enhance effective mixing and inter-phase mass transfer, and H 2 O 2 may be used effectively after decomposition. [50][51][52] On the other hand, too high temperatures are not good choice and might lead to auxiliary risk of explosion in the process, although high temperature enhances H 2 O 2 decomposition. Therefore, reaction at higher temperature should be carefully avoided.…”
Section: Ods Using Ilsmentioning
confidence: 99%
“…The trend is consistent with a previous study. 33 However, the reaction temperature of 30 C was considered as the optimal reaction temperature since low temperature ensures safety and low cost.…”
Section: Inuence Of the Reaction Temperature On Odsmentioning
confidence: 99%
“…[25][26][27][28] For instance, Li et al 29 synthesized 1.6Et 3 NHCl$FeCl 3 extract, which facilitated the desulfurization rate up to 87%. Chen et al 30 reported that [Hnmp]Cl/ZnCl 2 was applied in oxidative desulfurization and its desulfurization rate reached up to 99.9% for the model diesel oil. Li et al 31 reported that C 5 H 9 NO$0.3FeCl 3 was used as an extractant as well as a catalyst in ODS and the removal rate of DBT was 97% in 3 h. Chen et al 32 synthesized [C 4 mim]Cl/3ZnCl 2 and 99.9% sulphur-removal rate could be obtained.…”
Section: Introductionmentioning
confidence: 99%